ADMINISTRATIVE AND PHARMACEUTICAL SCREENING OF DIABETES MELLITUS PRESCRIPTIONS IN TYPE 2 DIABETES MELLITUS PATIENTS IN THE HOSPITAL X JEMBER. - Michael Nicoin DC Michael Nicoin DC; Shinta Mayasari (LPPM Universitas dr. Soebandi, 2025)
AbstractBackground: Pharmaceutical services are drug and clinical pharmacy services that enhance therapeutic effects and minimize the risk of medication errors. A form of pharmaceutical service is prescription screening. Prescription screening is a prescription review which is an activity of pharmacists in reviewing prescriptions which includes administration before the prescription is compounded. Another study conducted by Aryzki entitled